Delivery outcomes as a result of snoring as determined by standard sleep surveys. (December 2022) - Robertson, A; Makris, A; Johnson, P; Middleton, S; Norman, M; Sullivan, C; Hennessy, A
Background: Sleep-disordered breathing (SDB), is an umbrella term that encompasses obstructive sleep apnea (OSA), central sleep apnea (CSA) and hypoventilation. is common but studies in the pregnant population are limited. Data suggests relationships between OSA and preeclampsia, but the relationship between snoring and pregnancy outcomes is unknown. Methods: A prospective study of 2224 singleton pregnancies was undertaken. Women were questioned using the Berlin Questionnaire (BQ- 2 or more categories where the score is positive.) and the Epworth Sleepiness Scale (ESS >10/24), the results compared with pregnancy outcomes with regard to hypertension in pregnancy. Results: Women having symptoms raising the possibility of OSA defined by the BQ with a score >7 was 45.5%, and using ESS with a score >10, was 36%. The birth and neonatal outcomes for self-reported snoring and increased daytime sleepiness showed increased adverse outcomes notably increased caesarean section rates and low APGAR scores but not birth before 37 weeks of gestation. Conclusion: Using questionnaires designed for the general population, the prevalence of possible undiagnosed OSA is high in the pregnant population. The increased adverse delivery and neonatal outcomes for self-reported snoring and increased daytime sleepiness with these tools indicated the need for further investigation of the links between snoring SDB and pregnancy outcomes.